Isolation and Molecular Detection of Bovine Parainfluenza Virus Type 3 in Cattle in Serbia - Veljović Ljubiša; Knežević Aleksandra; Milić Nenad; Krnjaić Dejan; Miković Radoš; Zorić Andrea; Marković Maja; Milićević Vesna; Stamenković Miodrag; Stanojević Maja; Maksimović-Zorić Jelena; Petrović Tamaš; et al. (Acta Veterinaria, 2016)
The presence of bovine parainfluenza virus type 3 (BPIV3) was examined in 119 nasal swabs collected from cattle with severe respiratory infection. All samples were conducted for virus isolation on the MDBK cell line. The cytopathic effect was observed after 48h to 72h in cells inoculated with eight samples (8/119; 6.7%). The confirmation of isolated strains of BPIV3 was done by the virus-neutralization test. In addition, all samples of bovine nasal swabs were also examined for the presence of BPIV3 virus using RT-PCR with primers specific for the part of HN gene. The presence of BPIV3 was detected in eight samples (8/119; 6.7%) that were also positive upon virus isolation. The molecular characterization based on nucleotide sequencing of the part of the HN gene showed that all BPIV3 isolates belonged to genotype C of BPIV3. They branched in one distinct cluster with three different branches, but these branches were very similar to each other (98.1% to 99.8%). Serbian BPIV3c isolates were most similar to the Chinese BPIV3c isolates SD0805, SD0809 and SD0835 (from 97.92% to 99.7%), and to South Korean (12Q061), Japanese (HS9) and American (TVMDL16 and TVMDL20) BPIV3c strains (from 97.1% to 98.8%), and distinct from American (TVMDL15and TVMDL17) and Australian (Q5592) BPI3V genotype B strains (only 79.9% to 82.3% similarity), as well as from the genotype A BPIV3 strains from different countries published in GenBank.